Geronimo Stilton reporter. 4, The mummy with no name - Stilton, Geronimo (Geronimo Stilton reporter graphic novel, 2020)
When reports of a mummy terrorizing the New Mouse City Museum flood the Rodent's Gazette's telephone lines, Geronimo Stilton, editor-in-chief, searches for an explanation to prove that there is no mummy.